Addicted to the Thrill of the Virtual Hunt: Examining the Effects of Internet Addiction on the Cyberstalking Behaviors of Juveniles. Issue 8 (2nd August 2016) - Navarro, Jordana N.; Marcum, Catherine D.; Higgins, George E.; Ricketts, Melissa L.
ABSTRACT: The rapid advancement of technology has produced several substantial benefits that enrich individuals' lives, but some also note that technology has provided new methods to engage in crime—particularly stalking. This investigation was one of the first to explore whether a relationship existed between cyberstalking and a new phenomenon becoming a pressing issue in the lives of adolescents: Internet Addiction. High school students in a rural North Carolina country were surveyed about their Internet behaviors and experiences. After analysis, the results indicated there is a significant relationship between Internet Addiction and cyberstalking in adolescents.